(untitled) (E Conference Zone, 2022)
To radically change the attitude of the population to horse breeding, to give necessary and useful advice on horse breeding, to increase the population’s interest in horse breeding. To provide the population with ways to develop horse breeding in agriculture and sports. Development of horse breeding among the population